2021
DOI: 10.3389/feduc.2021.636067
|View full text |Cite
|
Sign up to set email alerts
|

FridaysForFuture as an Enactive Network: Collective Agency for the Transition Towards Sustainable Development

Abstract: In this article, we provide a theoretical conceptual analysis of FridaysForFuture (FFF) and of its effort in promoting the governance of socioeconomic transition toward sustainable development. FFF is a social movement that has received outstanding public recognition and visibility across the world in the last 2 years and is of great interest to educational research because it is largely composed of youngsters and appears to play a paideutic role in societal innovation. There is a growing but still limited bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…In this sense, studies have also shown that one of the greatest barriers to pro-environmental behaviour is a sense that individual efforts are insufficient to combat environmental crises such as climate change [79]. Consequently, some social movements are maturing, for example, the FridaysForFuture movement (FFF), where efforts are focused on promoting social change by going beyond the individual toward a collective agency [80], which is in accordance with this game's objective of cooperation. Moreover, after playing, our students expressed greater awareness about the environmental crisis; indicated also by an increase of awareness about the daily activities that they recognized as contributing to GC.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, studies have also shown that one of the greatest barriers to pro-environmental behaviour is a sense that individual efforts are insufficient to combat environmental crises such as climate change [79]. Consequently, some social movements are maturing, for example, the FridaysForFuture movement (FFF), where efforts are focused on promoting social change by going beyond the individual toward a collective agency [80], which is in accordance with this game's objective of cooperation. Moreover, after playing, our students expressed greater awareness about the environmental crisis; indicated also by an increase of awareness about the daily activities that they recognized as contributing to GC.…”
Section: Discussionmentioning
confidence: 99%
“…“Value co-creation” [ 109 ] and interactive engagement with customers might be a starting point. Social movements such as “FridaysForFuture” that have received public recognition and influenced public discourse [ 110 ] need more attention Geography of transitions: spaces, scales, places How transitions differ or are similar in various locations, and explaining how place-based factors enable and constrain the differences or similarities The current state of ST in a defined geographic area Factors influencing similarities or differences in a certain geographic area, also lack in how factors are influenced by geography Ethical aspects of transitions: distribution, justice, poverty Notions of equity and justice, human rights, well-being and social welfare, relations between humans and the natural world and how to distribute natural resources Ethical interactions between consumers and online systems Future research can consider welfare, resource distribution, equality, and justice. An ethical framework contains both classic and practical principles that can be borrowed; see example [ 111 ] Methodologies for transitions research Methodological approaches to investigate, solve, or propose solutions Solutions, methodologies, models Normally focus on in-depth single cases and therefore lack institutional theory.…”
Section: Resultsmentioning
confidence: 99%
“…The recent interest in policies promoting quality of life and wellbeing has generated a large amount of heterogenic proposals from different agencies and scholars – including non-formal collective agents, such as the social movement FridaysforFuture (Francesconi et al, 2021) – not always in line with the original intent of Nussbaum and Sen. Moreover, not all of them are consistent with each other.…”
Section: Discussionmentioning
confidence: 99%